Nonsustained ventricular tachycardia does not affect the prognosis of neuromuscular diseases: A preliminary and retrospective study. Issue 3 (16th April 2018) - Kamihara, Takahiro; Yasuma, Fumihiko; Murohara, Toyoaki
Abstract: Background: Nonsustained ventricular tachycardia (NSVT) is sometimes observed in patients with neuromuscular diseases (NMDs). The aim of this study was to assess the role of NSVT in the survival prognosis of NMD patients. Methods: We retrospectively analyzed the patients with NMDs who had undergone Holter ECG recordings at a single center between February and August 2012. Sixty‐eight patients were enrolled in this study. The 5 year follow‐up was assessed according to the cumulative event‐free rate. Results: Twenty‐one patients died during the follow‐up, seven of whom died by cardiac death. The Kaplan–Meier survival curve that compared the patients with NSVT and those without NSVT indicated the NSVT was not related to the rate of all causes of death or cardiac death in those patients with NMDs. The survival curve was not significantly changed after the adjustment by age and ejection fraction. Conclusion: No significant correlations between NSVT and the prognosis in patients with NMDs were found.